Hubungan Variasi Genetik Gen FADS pada Suku Sasak Terhadap Angka Kecukupan Gizi - Sasmitha Ajiningrum, Ridha; Gde Sri Adnyani, Luh; Agung Riatmojo, Andi; Eka Trie Sanggita, Vira; Rahmah , Siti (Jurnal Syntax Fusion, 2022)
One of the macronutrients needed by the human body is fat. Fatty acids are divided into two, namely saturated and unsaturated fatty acids. Based on the source of unsaturated fatty acids are divided into two, namely non-essential and essential. Essential fatty acids consist of omega-3 and omega-6 which are part of PUFAs. To determine the relationship of genetic variation of the FADS gene to the nutritional adequacy of long-chain polyunsaturated fatty acids (LC-PUFA) in children of the Sasak ethnic. Systematic reviews were carried out through scientific journals, government guidelines, online portals for journal publications such as Medscape, Google Scholar, PubMed, and Science Direct, with the keyword “Polyunsaturated Fatty Acid (PUFA)” There was a significant relationship between the FADS2 index (DHA: EPA ratio) and MDI score (r = 0.648, p < 0.059) in AG but not in GG genotype. Two genotype models were found, namely homozygous major allele (GG) of rs 174468 which was dominant and heterozygous allele (AG) of Sasak ethnicity. The levels of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in infants in the Sasak ethnic were found to be higher than infants in other areas. Sasak ethnic children get EPA and DHA from breast milk which contains a lot of DHA. Sources of omega-3 and 6 on the island of Lombok are sea fish, seaweed, and full-blooded shellfish.